Analysis of Factors Affecting the Incidence of Musculoskeletal Disorders (MSDs) among Rubber Factory Field Workers: A Literature Review - Arrohmansyah, Dimas; Utomo, Muhammad Aditya (Global Health Science Group, 2025)
Musculoskeletal disorders (MSDs) are common complaints experienced by field workers, especially in industrial sectors such as rubber factories that require heavy, repetitive physical activity and non-ergonomic working postures. These complaints have a negative impact on work productivity and quality of life of workers. This study is a literature review study by reviewing scientific articles from databases such as PubMed, ScienceDirect, and Google Scholar. Inclusion criteria include publications in the last 10 years (2015–2025) that discuss the relationship between risk factors and the incidence of MSDs in field workers in the industrial sector. Articles that are not available in full-text, are of low quality, or are irrelevant were excluded from the analysis. From the results of the review of 20 articles that met the criteria, it was found that the factors most often associated with the incidence of MSDs include ergonomic factors, individual factors. MSDs in rubber factory field workers are influenced by a combination of ergonomic, individual, and psychosocial factors. Prevention can be done through a work ergonomics approach, physical training, provision of work aids, and work stress management.